Respuesta :

Answer:

A.   x = 0, 14

B.   x = 12, -2

Step-by-step explanation:

A.

2x - 3       x + 6

    /      =      /

 x + 1        x - 2

 2x^2 - 7x + 6  =  x^2 + 7x + 6

-  x^2 - 7x - 6   -  x^2 - 7x - 6    

x^2 - 14x = 0        

( x + 0 ) = 0     ( x - 14 ) =  0

x = 0,                    +14     +14

                                x = 14

-----------------------------------------------------

B.

2               x

/     =         /

x          5x + 12

x^2 = 2( 5x + 12 )

x^2                   = 10x + 24

     - 10x - 24    - 10x - 24

x^2 - 10x - 24 = 0

( x - 12 ) = 0      ( x + 2) = 0

    +12     +12         -2     -2

x = 12,               x = -2

I hope this helps!